Kinematic analysis of the slap hitting technique in Division I softball players - Lund, R.; Ficklin, T.; Faga, J.; Reilly-Boccia, C. (The Sport Journal, 2015)
The purpose of this study was to provide a kinematic description of the phase parameters of the slap hitting technique and the interrelationships that may exist in Division I softball players. Video data were collected for all swings during a 15-game softball tournament in which six NCAA Division I teams played. A high-speed video camera filming at 300 Hz was located along the third base line recording every pitch. Only data from trials in which a slap swing attempt was made were kept, resulting in 200 trials. Three phases were identified; preparatory step, wind-up and swing. The duration of each phase (tPREP, tWIND-UP and tSWING, s) as well as the duration of the entire technique (tTOTAL, s), the forward velocity of the hips (vHIP, m/s) during the wind-up phase and the velocity of the bat at contact (vBAT, m/s) were obtained for each trial. Descriptive statistics were calculated for each of the variables and Pearson product moment correlations were used to examine the relationships among the variables. Several significant relationships were identified (p<0.05). The duration of the preparatory step phase has a direct effect on vHIP and vBAT. The duration of the wind-up and swing phases appear to be related to the timing of each individual trial and do not appear to play a role in vHIP and vBAT. Coaches should consider the role of the preparatory step phase on vHIP and vBAT when coaching different techniques such as the soft slap and the power slap.